High-excitation-efficiency nitride blue-green fluorescent powder, and preparation method and use thereof

CN122959025APending Publication Date: 2026-10-23YANTAI BRIGHT OPTOELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611091700.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0003]但现有氮氧化物蓝绿该类荧光粉在实际应用中存在以下明显的行业共性痛点:1)光衰远高于常规黄绿粉与红粉,灯具长期使用后显色指数快速下降;2)高温焙烧后破碎研磨会造成荧光粉颗粒表面产生大量破损、晶格缺陷增多,成为光衰与热猝灭中心;3)直接进行二次焙烧易出现超细颗粒烧结、颗粒粘连产生硬团聚,需再次破碎,进一步加剧表面损伤;4)硼酸干法混合易团聚,难以在颗粒表面形成均匀、连续的保护膜,耐湿热提升效果有限

Benefits of technology

1、本发明通过两级过筛(400目+800目)精准去除粗颗粒及超细颗粒,从源头避免了粗颗粒在后续过程中再次破碎引入晶格位错、层错等新缺陷,同时消除了高表面能超细颗粒易引发二次烧结的隐患;配合低温短时修复焙烧工艺,使破碎引入的表面晶格畸变得到有效愈合,显著降低了非辐射复合中心密度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959025A_ABST
    Figure CN122959025A_ABST
Patent Text Reader

Abstract

The application relates to a high-index nitride oxide blue-green fluorescent powder and a preparation method and application thereof, and belongs to the technical field of fluorescent powder. 1‑x Si2O2N2:Eu x 2+ 0.02 <= x <= 0.08. The preparation method of the high-index nitride oxide blue-green fluorescent powder comprises the following steps: uniform mixing of ingredients, high-temperature calcination, crushing and sorting, liquid-phase dispersion coating and secondary repair calcination. Through the synergistic technical path of screening impurities, liquid-phase uniform coating and low-temperature repair film forming, the multi-dimensional performance contradictions of fluorescent powder brightness, light decay, moisture resistance, index stability and particle size consistency are solved, the synergistic gain beyond simple superposition of each single means is achieved, and outstanding substantial progress and wide industrial application value are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high color rendering index (CRI) nitride blue-green phosphor, its preparation method and uses, and belongs to the field of phosphor technology. Background Technology

[0002] As people's demands for light quality continue to increase, high color rendering index (Ra≥95) lighting and full-spectrum LEDs have become important development directions in the lighting industry. (Note: The last part, "NOx blue-green phosphor BaSi2O2N2:Eu," appears to be unrelated and likely refers to a different product or technology.) 2+ Due to its high luminous efficiency, good color purity, and excellent chemical stability, it has become an irreplaceable blue-green band supplementary light material in high color rendering index (CRI) schemes.

[0003] However, existing nitrogen oxide blue-green phosphors have the following obvious common pain points in practical applications: 1) The light decay is much higher than that of conventional yellow-green and red phosphors, and the color rendering index drops rapidly after long-term use of lamps; 2) High-temperature calcination followed by crushing and grinding will cause a large number of damages on the surface of phosphor particles and an increase in lattice defects, becoming the center of light decay and thermal quenching; 3) Direct secondary calcination is prone to ultrafine particle sintering and particle adhesion, resulting in hard agglomeration, which requires further crushing and further aggravates surface damage; 4) Boric acid dry mixing is prone to agglomeration, making it difficult to form a uniform and continuous protective film on the particle surface, and the effect of improving resistance to damp heat is limited.

[0004] Current technologies primarily focus on primary formulation and doping optimization, without systematic improvements in areas such as damage repair, prevention of secondary sintering, uniform boric acid dispersion, and low-temperature short-time repair. Therefore, developing a method for preparing blue-green phosphors that can repair surface defects, prevent agglomeration, exhibit low light decay, and good resistance to damp heat is an urgent need in the high CRI LED market. Summary of the Invention

[0005] This invention provides a high color rendering index (CRI) nitride blue-green phosphor, its preparation method, and its uses to solve the technical problems existing in the prior art as described above.

[0006] The technical solution provided by this invention is as follows: One objective of this invention is to provide a high color rendering index (CRI) nitride blue-green phosphor with the chemical formula Ba. 1- x Si2O2N2:Eu x 2+ , where 0.02≤x≤0.08.

[0007] The second objective of this invention is to provide a method for preparing the high color rendering index (CRI) oxynitride blue-green phosphor as described above, comprising the following steps: (1) Mixing the ingredients: Weigh the raw materials BaCO3, SiO2, Si3N4 and Eu2O3, add the composite flux and mix evenly to obtain the raw material mixed powder; (2) High-temperature calcination: The raw material mixed powder is placed into a crucible and calcined at high temperature under a reducing atmosphere. After natural cooling, primary phosphor powder is obtained. (3) Crushing and sorting: After grinding the primary phosphor, it is sieved in two stages to obtain the sorted primary phosphor; (4) Liquid phase dispersion coating: Add boric acid aqueous solution to the sorted primary phosphor, stir and ultrasonically disperse evenly, filter and dry, so that boric acid is evenly dispersed on the surface of phosphor particles to obtain phosphor after dispersion treatment. (5) Secondary repair calcination: The dispersed phosphor is placed into a crucible and put into a high-temperature furnace. Secondary repair calcination is carried out under a reducing atmosphere and then cooled naturally to obtain high color rendering index nitrogen oxide blue-green phosphor.

[0008] Further, in step (1), the molar ratio of the raw materials BaCO3, SiO2, Si3N4, and Eu2O3 is 2(1). x):1:1:x, where 0.02≤x≤0.08.

[0009] Further, in step (1), the composite flux is a mixture of NH4Cl and BaF2, and the mass ratio of NH4Cl to BaF2 is 1~2:1~2; the added mass of the composite flux is 0.5%~2% of the total mass of the raw materials. Furthermore, in step (2), the high-temperature calcination is carried out by heating at a rate of 3~7℃ / min to 1400℃~1550℃ and holding for 4~6h. Furthermore, in step (3), the two-stage sieving involves first passing the material through a 400-mesh sieve to remove coarse particles, and then passing it through an 800-mesh sieve to remove fine particles.

[0010] The effect of adopting the above-mentioned further solutions is that coarse particles are removed first to avoid further breakage and reduce the generation of lattice defects, while fine particles are removed to reduce the surface energy of the particles and prevent sintering adhesion during secondary repair. Furthermore, in step (4), the mass-to-volume ratio of the boric acid aqueous solution is 0.01~0.03 g / ml, and the ratio of the sorted primary phosphor to the boric acid aqueous solution is 0.1~0.3 g: 1 ml.

[0011] Furthermore, in step (5), the secondary repair calcination is carried out by heating to 1300-1400℃ at a rate of 5-12℃ / min and holding for 1-3 hours.

[0012] Furthermore, the reducing atmosphere is a mixture of H2 and N2 with a volume fraction of 5% to 15% H2.

[0013] The third objective of this invention is to provide the use of the high color rendering index (CRI) oxynitride blue-green phosphor as described above, or the high CRI oxynitride blue-green phosphor prepared by the preparation method described above, in high CRI lighting, full-spectrum LEDs, educational lighting, medical lighting, and commercial high CRI lighting.

[0014] The technical solution provided by this invention has the following advantages compared with the prior art: 1. This invention precisely removes coarse and ultrafine particles through two-stage sieving (400 mesh + 800 mesh), preventing coarse particles from being broken again in subsequent processes and introducing new defects such as lattice dislocations and stacking faults. At the same time, it eliminates the hidden danger of secondary sintering caused by high surface energy ultrafine particles. Combined with a low-temperature short-time repair calcination process, the surface lattice distortions introduced by breakage are effectively healed, significantly reducing the density of non-radiative composite centers.

[0015] 2. This invention uses pure water to disperse boric acid in the aqueous phase. By utilizing the uniform distribution of boric acid in the aqueous phase, single-particle coating is achieved on the surface of each phosphor particle. During the low-temperature short-time calcination process, boric acid decomposes in situ to generate B2O3, which reacts with the oxide components such as SiO2 enriched on the surface of the phosphor particles to form a continuous, dense, and transparent B2O3-SiO2 glass-like protective film. This protective film has high chemical inertness, can effectively block the erosion of water vapor and oxygen, and has a controllable film thickness and a strong bond with the substrate, which can meet the stringent requirements of outdoor high humidity and high temperature lighting environments.

[0016] 3. While achieving surface lattice repair and glass film formation, this invention prevents any grain fusion or agglomeration between particles, maintaining a concentrated, uniform, and stable particle size distribution. The synergistic effect of two-stage sieving and the gentle liquid-phase coating-calcination process avoids the particle adhesion and particle size dispersion problems commonly found in traditional high-temperature solid-phase repair or gas-phase coating, providing good flowability and dispersibility for subsequent packaging processes, ensuring batch-to-batch consistency, and making it suitable for industrial mass production.

[0017] 4. The preparation method of this invention uses pure water as the dispersion medium throughout the entire process, without the need for organic solvents and without the emission of harmful byproducts; the three-step core process (two-stage sieving, liquid-phase dispersion coating and low-temperature short-time calcination) has a wide operating window, low equipment requirements, is easy to scale up, and has good economic and environmental friendliness, enabling stable and efficient large-scale supply.

[0018] 5. This invention, through a synergistic technical approach of sieving and impurity removal, uniform liquid-phase coating, and low-temperature repair film formation, simultaneously solves the multi-dimensional performance contradictions of phosphors, such as brightness, light decay, moisture resistance, color index stability, and particle size consistency. It achieves synergistic gains that exceed the simple superposition of individual methods, and has outstanding substantial progress and broad industrial application value. Attached Figure Description

[0019] Figure 1 SEM image of the high colorimetric index nitride blue-green phosphor prepared in Example 6 of the present invention; Figure 2 This is a SEM image of the nitrogen oxide blue-green phosphor prepared in Comparative Example 3 of the present invention. Detailed Implementation The principles and features of the present invention are described below with reference to examples. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention.

[0020] This invention provides a high color rendering index (CRI) nitrogen oxide blue-green phosphor with the chemical formula Ba. 1-x Si2O2N2:Eu x 2+ , where x = 0.05.

[0021] Example 1 A method for preparing a high color rendering index (CRI) oxynitride blue-green phosphor includes the following steps: (1) Mixing the ingredients: Weigh 187.4g of raw materials BaCO3, 30g of SiO2, 70g of Si3N4 and 8.8g of Eu2O3 according to the stoichiometric molar ratio BaCO3:SiO2:Si3N4:Eu2O3=0.95:0.5:0.5:0.025, add 1% of composite flux (NH4Cl:BaF2=1:1, w / w) to the total mass of raw materials, place in a double cone mixer and mix evenly to obtain raw material mixed powder; (2) High temperature calcination: The raw material mixed powder is loaded into a molybdenum crucible and heated to 1500℃ at a heating rate of 5℃ / min under a reducing atmosphere (a mixed gas of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6L / min). The temperature is held for 5h and then naturally cooled to obtain primary phosphor. (3) Crushing and sorting: After grinding the primary phosphor, first pass it through a 400-mesh sieve to remove coarse particles, and then pass it through an 800-mesh sieve to remove ultrafine particles, to obtain sorted primary phosphor; (4) Liquid phase dispersion coating: Boric acid is dissolved in pure water to prepare a 0.02 g / ml boric acid aqueous solution; the sorted primary phosphor is dispersed in the prepared boric acid aqueous solution (sorted primary phosphor: boric acid aqueous solution = 0.1 g: 1 ml), stirred at 500 r / min for 30 minutes, then ultrasonically dispersed at 50 kHz for 20 minutes, and then filtered to remove 80% of the boric acid aqueous solution. The filter cake is placed in an oven at 105 ℃ and dried for 3 hours to make the boric acid uniformly dispersed on the surface of the phosphor particles, thus obtaining the dispersed phosphor. (5) Secondary repair calcination: The dispersed phosphor is placed into a molybdenum crucible and placed in a high-temperature furnace. Under a reducing atmosphere (a mixture of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6 L / min), the temperature is raised to 1300℃ at a heating rate of 8℃ / min, held for 1 hour, and then cooled naturally to obtain a high color index nitrogen oxide blue-green phosphor. (6) Post-processing: Take 200g of high color rendering index nitrogen oxide blue-green phosphor and disperse it in 400g of pure water. Put it into a 1L plastic bottle and add 800g of zirconia balls with a particle size of 4~5mm. Ball mill it in a bottle roller (200r / min) until D50=19±2μm. After washing and drying, the finished phosphor is obtained.

[0022] Example 2 A method for preparing a high color rendering index (CRI) oxynitride blue-green phosphor includes the following steps: (1) Mixing the ingredients: Weigh 187.4g of raw materials BaCO3, 30g of SiO2, 70g of Si3N4 and 8.8g of Eu2O3 according to the stoichiometric molar ratio BaCO3:SiO2:Si3N4:Eu2O3=0.95:0.5:0.5:0.025, add 0.5% of composite flux (NH4Cl:BaF2=1:2, w / w) to the raw materials, place them in a double cone mixer and mix them evenly to obtain the raw material mixed powder; (2) High temperature calcination: The raw material mixed powder is loaded into a molybdenum crucible and heated to 1400℃ at a heating rate of 3℃ / min under a reducing atmosphere (a mixed gas of H2-N2 with a volume fraction of 5% H2 and a flow rate of 1.6L / min). The temperature is held for 4 hours and then naturally cooled to obtain primary phosphor. (3) Crushing and sorting: After grinding the primary phosphor, first pass it through a 400-mesh sieve to remove coarse particles, and then pass it through an 800-mesh sieve to remove ultrafine particles, to obtain sorted primary phosphor; (4) Liquid phase dispersion coating: Boric acid is dissolved in pure water to prepare a 0.01 g / ml boric acid aqueous solution; the sorted primary phosphor is dispersed in the prepared boric acid aqueous solution (sorted primary phosphor: boric acid aqueous solution = 0.2 g: 1 ml), stirred at 500 r / min for 30 minutes, then ultrasonically dispersed at 50 kHz for 20 minutes, and then filtered to remove 80% of the boric acid aqueous solution. The filter cake is placed in an oven at 105 ℃ and dried for 3 hours to make the boric acid uniformly dispersed on the surface of the phosphor particles, thus obtaining the dispersed phosphor. (5) Secondary repair calcination: The dispersed phosphor is placed into a molybdenum crucible and placed in a high-temperature furnace. Under a reducing atmosphere (a mixture of H2-N2 with a volume fraction of 5% H2 and a flow rate of 1.6 L / min), the temperature is raised to 1350℃ at a heating rate of 5℃ / min, held for 2 hours, and then cooled naturally to obtain a high color index nitrogen oxide blue-green phosphor. (6) Post-processing: Take 200g of high color rendering index nitrogen oxide blue-green phosphor and disperse it in 400g of pure water. Put it into a 1L plastic bottle and add 800g of zirconia balls with a particle size of 4~5mm. Ball mill it in a bottle roller (200r / min) until D50=19±2μm. After washing and drying, the finished phosphor is obtained. Example 3 A method for preparing a high color rendering index (CRI) oxynitride blue-green phosphor includes the following steps: (1) Mixing the ingredients: Weigh 187.4g of raw materials BaCO3, 30g of SiO2, 70g of Si3N4 and 8.8g of Eu2O3 according to the stoichiometric molar ratio BaCO3:SiO2:Si3N4:Eu2O3=0.95:0.5:0.5:0.025, add 2% of the total mass of raw materials composite flux (NH4Cl:BaF2=2:1, w / w), place in a double cone mixer and mix evenly to obtain raw material mixed powder; (2) High temperature calcination: The raw material mixed powder is loaded into a molybdenum crucible and heated to 1550℃ at a heating rate of 7℃ / min under a reducing atmosphere (a mixed gas of H2-N2 with a volume fraction of 15% H2 and a flow rate of 1.6L / min). The temperature is held for 6 hours and then naturally cooled to obtain primary phosphor. (3) Crushing and sorting: After grinding the primary phosphor, first pass it through a 400-mesh sieve to remove coarse particles, and then pass it through an 800-mesh sieve to remove ultrafine particles, to obtain sorted primary phosphor; (4) Liquid phase dispersion coating: Boric acid is dissolved in pure water to prepare a 0.03 g / ml boric acid aqueous solution; the sorted primary phosphor is dispersed in the prepared boric acid aqueous solution (sorted primary phosphor: boric acid aqueous solution = 0.3 g: 1 ml), stirred at 500 r / min for 30 minutes, then ultrasonically dispersed at 50 kHz for 20 minutes, and then filtered to remove 80% of the boric acid aqueous solution. The filter cake is placed in an oven at 105 ℃ and dried for 3 hours to make the boric acid uniformly dispersed on the surface of the phosphor particles, thus obtaining the dispersed phosphor. (5) Secondary repair calcination: The dispersed phosphor is placed into a molybdenum crucible and placed in a high-temperature furnace. Under a reducing atmosphere (a mixture of H2-N2 with a volume fraction of 15% H2 and a flow rate of 1.6 L / min), the temperature is increased to 1400℃ at a heating rate of 12℃ / min, held for 3 hours, and then naturally cooled to obtain a high color index nitrogen oxide blue-green phosphor. (6) Post-processing: Take 200g of high color rendering index nitrogen oxide blue-green phosphor and disperse it in 400g of pure water. Put it into a 1L plastic bottle and add 800g of zirconia balls with a particle size of 4~5mm. Ball mill it in a bottle roller (200r / min) until D50=19±2μm. After washing and drying, the finished phosphor is obtained.

[0023] Example 4 A method for preparing a high color rendering index (CRI) oxynitride blue-green phosphor includes the following steps: (1) Mixing the ingredients: Weigh 187.4g of raw materials BaCO3, 30g of SiO2, 70g of Si3N4 and 8.8g of Eu2O3 according to the stoichiometric molar ratio BaCO3:SiO2:Si3N4:Eu2O3=0.95:0.5:0.5:0.025, add 1% of composite flux (NH4Cl:BaF2=1:1, w / w) to the total mass of raw materials, place in a double cone mixer and mix evenly to obtain raw material mixed powder; (2) High temperature calcination: The raw material mixed powder is loaded into a molybdenum crucible and heated to 1500℃ at a heating rate of 5℃ / min under a reducing atmosphere (a mixed gas of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6L / min). The temperature is held for 5h and then naturally cooled to obtain primary phosphor. (3) Crushing and sorting: After grinding the primary phosphor, first pass it through a 400-mesh sieve to remove coarse particles, and then pass it through an 800-mesh sieve to remove ultrafine particles, to obtain sorted primary phosphor; (4) Liquid phase dispersion coating: Boric acid is dissolved in pure water to prepare a 0.02 g / ml boric acid aqueous solution; the sorted primary phosphor is dispersed in the prepared boric acid aqueous solution (sorted primary phosphor: boric acid aqueous solution = 0.2 g: 1 ml), stirred at 500 r / min for 30 minutes, then ultrasonically dispersed at 50 kHz for 20 minutes, and then 80% of the boric acid aqueous solution is filtered off. The filter cake is placed in an oven at 105 ℃ and dried for 3 hours to make the boric acid uniformly dispersed on the surface of the phosphor particles, thus obtaining the dispersed phosphor. (5) Secondary repair calcination: The dispersed phosphor is placed into a molybdenum crucible and placed in a high-temperature furnace. Under a reducing atmosphere (a mixture of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6 L / min), the temperature is raised to 1350℃ at a heating rate of 8℃ / min, held for 1 hour, and then cooled naturally to obtain a high color index nitrogen oxide blue-green phosphor. (6) Post-processing: Take 200g of high color rendering index nitrogen oxide blue-green phosphor and disperse it in 400g of pure water. Put it into a 1L plastic bottle and add 800g of zirconia balls with a particle size of 4~5mm. Ball mill it in a bottle roller (200r / min) until D50=19±2μm. After washing and drying, the finished phosphor is obtained.

[0024] Example 5 A method for preparing a high color rendering index (CRI) oxynitride blue-green phosphor includes the following steps: (1) Mixing the ingredients: Weigh 187.4g of raw materials BaCO3, 30g of SiO2, 70g of Si3N4 and 8.8g of Eu2O3 according to the stoichiometric molar ratio BaCO3:SiO2:Si3N4:Eu2O3=0.95:0.5:0.5:0.025, add 1% of composite flux (NH4Cl:BaF2=1:1, w / w) to the total mass of raw materials, place in a double cone mixer and mix evenly to obtain raw material mixed powder; (2) High temperature calcination: The raw material mixed powder is loaded into a molybdenum crucible and heated to 1500℃ at a heating rate of 5℃ / min under a reducing atmosphere (a mixed gas of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6L / min). The temperature is held for 5h and then naturally cooled to obtain primary phosphor. (3) Crushing and sorting: After grinding the primary phosphor, first pass it through a 400-mesh sieve to remove coarse particles, and then pass it through an 800-mesh sieve to remove ultrafine particles, to obtain sorted primary phosphor; (4) Liquid phase dispersion coating: Boric acid is dissolved in pure water to prepare a 0.02 g / ml boric acid aqueous solution; the sorted primary phosphor is dispersed in the prepared boric acid aqueous solution (sorted primary phosphor: boric acid aqueous solution = 0.2 g: 1 ml), stirred at 500 r / min for 30 minutes, then ultrasonically dispersed at 50 kHz for 20 minutes, and then 80% of the boric acid aqueous solution is filtered off. The filter cake is placed in an oven at 105 ℃ and dried for 3 hours to make the boric acid uniformly dispersed on the surface of the phosphor particles, thus obtaining the dispersed phosphor. (5) Secondary repair calcination: The dispersed phosphor is placed into a molybdenum crucible and placed in a high-temperature furnace. Under a reducing atmosphere (a mixture of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6 L / min), the temperature is increased to 1400℃ at a heating rate of 8℃ / min, held for 1 hour, and then cooled naturally to obtain a high color index nitrogen oxide blue-green phosphor. (6) Post-processing: Take 200g of high color rendering index nitrogen oxide blue-green phosphor and disperse it in 400g of pure water. Put it into a 1L plastic bottle and add 800g of zirconia balls with a particle size of 4~5mm. Ball mill it in a bottle roller (200r / min) until D50=19±2μm. After washing and drying, the finished phosphor is obtained.

[0025] Example 6 A method for preparing a high color rendering index (CRI) oxynitride blue-green phosphor includes the following steps: (1) Mixing the ingredients: Weigh 187.4g of raw materials BaCO3, 30g of SiO2, 70g of Si3N4 and 8.8g of Eu2O3 according to the stoichiometric molar ratio BaCO3:SiO2:Si3N4:Eu2O3=0.95:0.5:0.5:0.025, add 1% of composite flux (NH4Cl:BaF2=1:1, w / w) to the total mass of raw materials, place in a double cone mixer and mix evenly to obtain raw material mixed powder; (2) High temperature calcination: The raw material mixed powder is loaded into a molybdenum crucible and heated to 1500℃ at a heating rate of 5℃ / min under a reducing atmosphere (a mixed gas of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6L / min). The temperature is held for 5h and then naturally cooled to obtain primary phosphor. (3) Crushing and sorting: After grinding the primary phosphor, first pass it through a 400-mesh sieve to remove coarse particles, and then pass it through an 800-mesh sieve to remove ultrafine particles, to obtain sorted primary phosphor; (4) Liquid phase dispersion coating: Boric acid is dissolved in pure water to prepare a 0.02 g / ml boric acid aqueous solution; the sorted primary phosphor is dispersed in the prepared boric acid aqueous solution (sorted primary phosphor: boric acid aqueous solution = 0.2 g: 1 ml), stirred at 500 r / min for 30 minutes, then ultrasonically dispersed at 50 kHz for 20 minutes, and then 80% of the boric acid aqueous solution is filtered off. The filter cake is placed in an oven at 105 ℃ and dried for 3 hours to make the boric acid uniformly dispersed on the surface of the phosphor particles, thus obtaining the dispersed phosphor. (5) Secondary repair calcination: The dispersed phosphor is placed into a molybdenum crucible and placed in a high-temperature furnace. Under a reducing atmosphere (a mixture of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6 L / min), the temperature is increased to 1350℃ at a heating rate of 8℃ / min, held for 2 hours, and then cooled naturally to obtain a high color index nitrogen oxide blue-green phosphor. (6) Post-processing: Take 200g of high color rendering index nitrogen oxide blue-green phosphor and disperse it in 400g of pure water. Put it into a 1L plastic bottle and add 800g of zirconia balls with a particle size of 4~5mm. Ball mill it in a bottle roller (200r / min) until D50=19±2μm. After washing and drying, the finished phosphor is obtained.

[0026] Example 7 A method for preparing a high color rendering index (CRI) oxynitride blue-green phosphor includes the following steps: (1) Mixing the ingredients: Weigh 187.4g of raw materials BaCO3, 30g of SiO2, 70g of Si3N4 and 8.8g of Eu2O3 according to the stoichiometric molar ratio BaCO3:SiO2:Si3N4:Eu2O3=0.95:0.5:0.5:0.025, add 1% of composite flux (NH4Cl:BaF2=1:1, w / w) to the total mass of raw materials, place in a double cone mixer and mix evenly to obtain raw material mixed powder; (2) High temperature calcination: The raw material mixed powder is loaded into a molybdenum crucible and heated to 1500℃ at a heating rate of 5℃ / min under a reducing atmosphere (a mixed gas of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6L / min). The temperature is held for 5h and then naturally cooled to obtain primary phosphor. (3) Crushing and sorting: After grinding the primary phosphor, first pass it through a 400-mesh sieve to remove coarse particles, and then pass it through an 800-mesh sieve to remove ultrafine particles, to obtain sorted primary phosphor; (4) Liquid phase dispersion coating: Boric acid is dissolved in pure water to prepare a 0.02 g / ml boric acid aqueous solution; the sorted primary phosphor is dispersed in the prepared boric acid aqueous solution (sorted primary phosphor: boric acid aqueous solution = 0.2 g: 1 ml), stirred at 500 r / min for 30 minutes, then ultrasonically dispersed at 50 kHz for 20 minutes, and then 80% of the boric acid aqueous solution is filtered off. The filter cake is placed in an oven at 105 ℃ and dried for 3 hours to make the boric acid uniformly dispersed on the surface of the phosphor particles, thus obtaining the dispersed phosphor. (5) Secondary repair calcination: The dispersed phosphor is placed into a molybdenum crucible and placed in a high-temperature furnace. Under a reducing atmosphere (a mixture of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6 L / min), the temperature is raised to 1350℃ at a heating rate of 8℃ / min, held for 3 hours, and then naturally cooled to obtain a high color index nitrogen oxide blue-green phosphor. (6) Post-processing: Take 200g of high color rendering index nitrogen oxide blue-green phosphor and disperse it in 400g of pure water. Put it into a 1L plastic bottle and add 800g of zirconia balls with a particle size of 4~5mm. Ball mill it in a bottle roller (200r / min) until D50=19±2μm. After washing and drying, the finished phosphor is obtained.

[0027] Comparative Example 1 A method for preparing a nitrogen oxide blue-green phosphor includes the following steps: (1) Mixing the ingredients: Weigh 187.4g of raw materials BaCO3, 30g of SiO2, 70g of Si3N4 and 8.8g of Eu2O3 according to the stoichiometric molar ratio BaCO3:SiO2:Si3N4:Eu2O3=0.95:0.5:0.5:0.025, add 1% of composite flux (NH4Cl:BaF2=1:1, w / w) to the total mass of raw materials, place in a double cone mixer and mix evenly to obtain raw material mixed powder; (2) High temperature calcination: The raw material mixed powder is loaded into a molybdenum crucible and heated to 1500℃ at a heating rate of 5℃ / min under a reducing atmosphere (a mixed gas of H2-N2 with a volume fraction of 10% and a flow rate of 1.6L / min). The temperature is held for 5h and then naturally cooled to obtain primary nitrogen oxide blue-green phosphor. (3) Post-processing: Take 200g of primary nitrogen oxide blue-green phosphor and disperse it in 400g of pure water. Put it into a 1L plastic bottle and add 800g of zirconia balls with a particle size of 4~5mm. Grind the mixture in a tumbler machine (200r / min) until D50=19±2μm. After washing and drying, the finished phosphor is obtained.

[0028] Comparative Example 2 A method for preparing a nitrogen oxide blue-green phosphor includes the following steps: (1) Mixing the ingredients: Weigh 187.4g of raw materials BaCO3, 30g of SiO2, 70g of Si3N4 and 8.8g of Eu2O3 according to the stoichiometric molar ratio BaCO3:SiO2:Si3N4:Eu2O3=0.95:0.5:0.5:0.025, add 1% of composite flux (NH4Cl:BaF2=1:1, w / w) to the total mass of raw materials, place in a double cone mixer and mix evenly to obtain raw material mixed powder; (2) High temperature calcination: The raw material mixed powder is loaded into a molybdenum crucible and heated to 1500℃ at a heating rate of 5℃ / min under a reducing atmosphere (a mixed gas of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6L / min). The temperature is held for 5h and then naturally cooled to obtain primary phosphor. (3) Secondary repair calcination: The primary phosphor is loaded into a molybdenum crucible and placed in a high-temperature furnace. Under a reducing atmosphere (a mixture of H2-N2 with a volume fraction of 10% and a flow rate of 1.6 L / min), the temperature is increased to 1350℃ at a heating rate of 8℃ / min, held for 2 hours, and then cooled naturally to obtain nitrogen oxide blue-green phosphor. (4) Post-processing: Take 200g of nitrogen oxide blue-green phosphor and disperse it in 400g of pure water, put it into a 1L plastic bottle, add 800g of zirconia balls with a particle size of 4~5mm, and ball mill it in a bottle roller (200r / min) until D50=19±2μm. After washing and drying, the finished phosphor is obtained.

[0029] Comparative Example 3 A method for preparing a nitrogen oxide blue-green phosphor includes the following steps: (1) Mixing the ingredients: Weigh 187.4g of raw materials BaCO3, 30g of SiO2, 70g of Si3N4 and 8.8g of Eu2O3 according to the stoichiometric molar ratio BaCO3:SiO2:Si3N4:Eu2O3=0.95:0.5:0.5:0.025, add 1% of composite flux (NH4Cl:BaF2=1:1, w / w) to the total mass of raw materials, place in a double cone mixer and mix evenly to obtain raw material mixed powder; (2) High temperature calcination: The raw material mixed powder is loaded into a molybdenum crucible and heated to 1500℃ at a heating rate of 5℃ / min under a reducing atmosphere (a mixed gas of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6L / min). The temperature is held for 5h and then naturally cooled to obtain primary phosphor. (3) Secondary repair calcination: The primary phosphor is mixed with boric acid at a mass ratio of 0.4%, then ground into a fine powder using an agate mortar and placed into a molybdenum crucible. The crucible is then placed in a high-temperature furnace and heated to 1350°C at a heating rate of 8°C / min under a reducing atmosphere (a mixture of H2-N2 with a volume fraction of 10% and a flow rate of 1.6 L / min). The temperature is maintained for 2 hours and then naturally cooled to obtain nitrogen oxide blue-green phosphor. (4) Post-processing: Take 200g of nitrogen oxide blue-green phosphor and disperse it in 400g of pure water, put it into a 1L plastic bottle, add 800g of zirconia balls with a particle size of 4~5mm, and ball mill it in a bottle roller (200r / min) until D50=19±2μm. After washing and drying, the finished phosphor is obtained.

[0030] Comparative Example 4 A method for preparing a nitrogen oxide blue-green phosphor includes the following steps: (1) Mixing the ingredients: Weigh 187.4g of raw materials BaCO3, 30g of SiO2, 70g of Si3N4 and 8.8g of Eu2O3 according to the stoichiometric molar ratio BaCO3:SiO2:Si3N4:Eu2O3=0.95:0.5:0.5:0.025, add 1% of composite flux (NH4Cl:BaF2=1:1, w / w) to the total mass of raw materials, place in a double cone mixer and mix evenly to obtain raw material mixed powder; (2) High temperature calcination: The raw material mixed powder is loaded into a molybdenum crucible and heated to 1500℃ at a heating rate of 5℃ / min under a reducing atmosphere (a mixed gas of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6L / min). The temperature is held for 5h and then naturally cooled to obtain primary phosphor. (3) Crushing and sorting: After grinding the primary phosphor, first pass it through a 400-mesh sieve to remove coarse particles, and then pass it through an 800-mesh sieve to remove ultrafine particles, to obtain sorted primary phosphor; (4) Secondary repair calcination: The sorted primary phosphor is loaded into a molybdenum crucible and placed in a high-temperature furnace. Under a reducing atmosphere (a mixture of H2-N2 with a volume fraction of 10% and a flow rate of 1.6 L / min), the temperature is increased to 1350℃ at a heating rate of 8℃ / min, held for 2 hours, and then cooled naturally to obtain nitrogen oxide blue-green phosphor. (5) Post-processing: Take 200g of nitrogen oxide blue-green phosphor and disperse it in 400g of pure water, put it into a 1L plastic bottle, add 800g of zirconia balls with a particle size of 4~5mm, and ball mill it in a bottle roller (200r / min) until D50=19±2μm. After washing and drying, the finished phosphor is obtained.

[0031] Comparative Example 5 A method for preparing a nitrogen oxide blue-green phosphor includes the following steps: (1) Mixing the ingredients: Weigh 187.4g of raw materials BaCO3, 30g of SiO2, 70g of Si3N4 and 8.8g of Eu2O3 according to the stoichiometric molar ratio BaCO3:SiO2:Si3N4:Eu2O3=0.95:0.5:0.5:0.025, add 1% of composite flux (NH4Cl:BaF2=1:1, w / w) to the total mass of raw materials, place in a double cone mixer and mix evenly to obtain raw material mixed powder; (2) High temperature calcination: The raw material mixed powder is loaded into a molybdenum crucible and heated to 1500℃ at a heating rate of 5℃ / min under a reducing atmosphere (a mixed gas of H2-N2 with a volume fraction of 10% H2 and a flow rate of 1.6L / min). The temperature is held for 5h and then naturally cooled to obtain primary phosphor. (3) Crushing and sorting: After grinding the primary phosphor, first pass it through a 400-mesh sieve to remove coarse particles, and then pass it through an 800-mesh sieve to remove ultrafine particles, to obtain sorted primary phosphor; (4) Secondary repair calcination: The sorted primary phosphor is mixed with 0.4% by mass of boric acid that has been finely ground through 400 mesh, placed in a molybdenum crucible, and placed in a high-temperature furnace. Under a reducing atmosphere (a mixture of H2-N2 with a volume fraction of 10% and a flow rate of 1.6 L / min), the temperature is raised to 1350℃ at a heating rate of 8℃ / min, held for 2 hours, and then naturally cooled to obtain nitrogen oxide blue-green phosphor. (5) Post-processing: Take 200g of nitrogen oxide blue-green phosphor and disperse it in 400g of pure water, put it into a 1L plastic bottle, add 800g of zirconia balls with a particle size of 4~5mm, and ball mill it in a bottle roller (200r / min) until D50=19±2μm. After washing and drying, the finished phosphor is obtained.

[0032] Performance testing: 1. Relative brightness: Excited with a blue LED chip with an emission peak wavelength of 450-452.5nm, Shin-Etsu KER-2000 adhesive was selected, and the mixture was prepared by mixing adhesive, nitride red powder, YAG yellow-green powder, and nitride blue-green powder at a mass ratio of 10:0.2:2:0.35. The mixture was then encapsulated onto the chip, dried at 150℃ for 2 hours, and then the initial brightness was tested using a Hangzhou Yuanfang USB4000 spectrometer. 2. Brightness retention rate after 1000h aging: After aging the packaged LEDs in the TEM1880 high and low temperature alternating damp heat test chamber of Shanghai Yishuo Experimental Instruments at 85℃ / 85% RH for 1000h, the luminous flux was tested using a USB4000 spectrometer from Hangzhou Yuanfang. The aging retention rate (%) = (brightness after aging / initial brightness) × 100. 3. Particle size D50: Detected using a Beckman Coulter LS13320 laser particle size analyzer; 4. Powder state after secondary repair and calcination: Observed using a KYKY2800B scanning electron microscope from CAS Instruments.

[0033] The test results are shown in Table 1.

[0034] Table 1 Performance Test Results

[0035] As can be seen from Table 1, the high color rendering index (CRI) blue-green phosphor prepared in the embodiments of this invention exhibits superior overall performance compared to the comparative samples. The series of samples in the embodiments not only maintained relatively high initial brightness but also achieved good aging retention. In particular, the optimized secondary repair calcination temperature and holding time in Example 6 demonstrated optimal overall performance, fully demonstrating the effectiveness of the secondary repair calcination and the further enhancing effect of liquid-phase dispersed boric acid on the secondary repair calcination. This also verifies the scientific nature of the technical solution of this invention and the synergy of its various innovative points.

[0036] In contrast, in Comparative Example 1, without secondary calcination after crushing, the phosphor exhibited low initial brightness and poor brightness retention after aging. This was attributed to the extensive surface damage caused by the crushing process, leading to increased lattice defects that became centers for light decay and thermal quenching. Comparative Examples 2 and 4 also showed that while secondary calcination without boric acid improved both initial brightness and aging, the surface repair effect was limited due to the absence of boric acid as a flux. Comparative Examples 3 and 5 demonstrated that secondary calcination with boric acid further enhanced both initial brightness and aging. However, the solid-phase boric acid could not be evenly dispersed across the phosphor particles, resulting in severe particle agglomeration after secondary calcination. After sorting, particle agglomeration was significantly reduced, demonstrating that sorting alone was insufficient, and simply adding boric acid did not yield satisfactory results. Only by combining these methods could the synergistic effect of crushing and sorting, liquid-phase boric acid dispersion, and secondary calcination be fully realized.

[0037] From SEM characterization, the high colorimetric blue-green phosphor prepared in Example 6 of this invention (such as...) Figure 1 Not only are the particles regular in morphology and without obvious agglomeration, but their surfaces are also smooth and crack-free, exhibiting excellent uniformity; while the blue-green phosphor prepared in Comparative Example 3 (such as...) Figure 2 The particles are of varying sizes, with severe aggregation of fine particles.

[0038] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high color rendering index nitride oxide blue-green fluorescent powder, characterized in that, Ba 1-x Si2O2N2:Eu x 2+ wherein 0.02≤x≤0.

08.

2. The method for preparing the high color rendering index (CRI) nitride blue-green phosphor as described in claim 1, characterized in that, Includes the following steps: (1) Mixing the ingredients: Weigh the raw materials BaCO3, SiO2, Si3N4 and Eu2O3, add the composite flux and mix evenly to obtain the raw material mixed powder; (2) High-temperature calcination: The raw material mixed powder is placed into a crucible and calcined at high temperature under a reducing atmosphere. After natural cooling, primary phosphor powder is obtained. (3) Crushing and sorting: After grinding the primary phosphor, it is sieved in two stages to obtain the sorted primary phosphor; (4) Liquid phase dispersion coating: The sorted primary phosphor is dispersed in a boric acid aqueous solution, stirred and ultrasonically dispersed evenly, filtered and dried so that the boric acid is evenly dispersed on the surface of the phosphor particles to obtain the phosphor after dispersion treatment. (5) Secondary repair calcination: The dispersed phosphor is placed into a crucible and put into a high-temperature furnace. Secondary repair calcination is carried out under a reducing atmosphere and then cooled naturally to obtain high color rendering index nitrogen oxide blue-green phosphor.

3. The method for preparing high color rendering nitrogen oxide blue-green fluorescent powder according to claim 2, characterized in that, In step (1), the molar ratio of the raw materials BaCO3, SiO2, Si3N4, Eu2O3 is 2(1 x): 1 : 1 : x, where 0.02 < x < 0.

08.

4. The method for preparing high color rendering nitrogen oxide blue-green fluorescent powder according to claim 2, characterized in that, In step (1), the composite flux is a mixture of NH4Cl and BaF2, with a mass ratio of NH4Cl to BaF2 of 1~2:1~2; the mass of the composite flux added is 0.5%~2% of the total mass of the raw materials.

5. The method for preparing the high color rendering index (CRI) nitride blue-green phosphor according to claim 2, characterized in that, In step (2), the high-temperature roasting is carried out by heating the temperature to 1400℃~1550℃ at a heating rate of 3~7℃ / min and holding it for 4~6h.

6. The method for preparing the high color rendering index (CRI) nitride blue-green phosphor according to claim 2, characterized in that, In step (3), the two-stage sieving involves first passing the material through a 400-mesh sieve to remove coarse particles, and then passing it through an 800-mesh sieve to remove fine particles.

7. The method for preparing the high color rendering index (CRI) nitride blue-green phosphor according to claim 2, characterized in that, In step (4), the mass-to-volume ratio of boric acid aqueous solution is 0.01~0.03 g / ml, and the ratio of the amount of primary phosphor after sorting to the amount of boric acid aqueous solution is 0.1~0.3 g: 1 ml.

8. The method for preparing the high color rendering index (CRI) nitride blue-green phosphor according to claim 2, characterized in that, In step (5), the secondary repair calcination is carried out by heating the temperature to 1300-1400℃ at a rate of 5-12℃ / min and holding it for 1-3 hours. 9.The method for preparing high color rendering nitrogen oxide blue-green fluorescent powder according to claim 2, characterized in that, The reducing atmosphere is a mixture of H2 and N2 with a volume fraction of 5% to 15% H2.

10. The use of the high color rendering index (CRI) oxynitride blue-green phosphor as described in claim 1 or the high CRI oxynitride blue-green phosphor prepared by any one of the preparation methods described in claims 2 to 8 in high CRI lighting, full-spectrum LEDs, educational lighting, medical lighting, and commercial high CRI lighting.